Closing the Licensing and Permit Regulatory Implementation Gap at the Sub-national Level in Bosnia and Herzegovina - Sahovic, Tarik (International Finance Corporation, Washington, DC, 2015)
Bosnia and Herzegovina (BiH) is classified as a Fragile and Conflict-Affected State. It has a complex government structure which is plagued with significant political turmoil each election cycle. BiH comprises the national (federal) level government, and two entities, the Federation BiH, Republika Srpska (RS), and Brcko District, all of which have strong legislative powers aff ecting day-to-day business operations. The Federation BiH is further divided into 10 cantons, each with their own government and legislative powers, although ultimately they are governed by the laws of the Federation BiH. Both the Federation BiH and RS are further subdivided into 143 cities and municipalities, each with their own municipal councils. Such a complex structure gives rise to overlapping competencies, conflicting legislative provisions, and a regulatory implementationgap at the sub-national level. The aim of this paper is to analyze and describe the approach, process and tools used by the team in identifying the problem of ambiguity in the text and the inconsistency of application of the same legislation across several BiH jurisdictions; and how the team’s decisions, activities and actions contributed to and influenced the results, that is to say in closing the regulatory implementation gaps at the sub-national level. The study also revealed the causal effect of the team’s efforts in terms of enabling the private sector to realize real benefits from the implemented reforms. The study consists of four parts. The first part details how the team identified the existence of a regulatory implementation gap and its causes. The second part analyses and describes the process of addressing the specific regulatory implementation gap identified in part one. The third part provides details of the process of the regulatory simplification the team used to address the regulatory implementation gap across jurisdictions, and to link these reforms with a reduction of the administrative burden and increased transparency. Finally, the study also distills the lessons learned during this process that may be relevant for similar situations and environments elsewhere in the future. Part four cites those lessons.